Inflammatory profile of convalescent plasma to treat COVID: Impact of amotosalen/UVA pathogen reduction technology - Cognasse, Fabrice; Hamzeh-Cognasse, Hind; Duchez, Anne-Claire; Shurko, Natalia; Eyraud, Marie-Ange; Arthaud, Charles-Antoine; Prier, Amélie; Heestermans, Marco; Hequet, Olivier; Bonneaudeau, Brigitte; Rochette-Eribon, Sandrine; Teyssier, Françoise; et al. (Frontiers in Immunology, 2022)
Blood products in therapeutic transfusion are now commonly acknowledged to contain biologically active constituents during the processes of preparation. In the midst of a worldwide COVID-19 pandemic, preliminary evidence suggests that convalescent plasma may lessen the severity of COVID-19 if administered early in the disease, particularly in patients with profound B-cell lymphopenia and prolonged COVID-19 symptoms. This study examined the influence of photochemical Pathogen Reduction Treatment (PRT) using amotosalen‐HCl and UVA light in comparison with untreated control convalescent plasma (n= 72 – paired samples) - cFFP, regarding soluble inflammatory factors: sCD40L, IFN-alpha, IFN-beta, IFN-gamma, IL-1 beta, IL-6, IL-8, IL-10, IL-18, TNF-alpha and ex-vivo inflammatory bioactivity on endothelial cells. We didn’t observe significant modulation of the majority of inflammatory soluble factors (8 of 10 molecules tested) pre- or post-PRT. We noted that IL-8 concentrations were significantly decreased in cFFP with PRT, whereas the IL-18 concentration was increased by PRT. In contrast, endothelial cell release of IL-6 was similar whether cFFP was pre-treated with or without PRT. Expression of CD54 and CD31 in the presence of cFFP were similar to control levels, and both were significant decreased in when cFFP had been pre-treated by PRT. It will be interesting to continue investigations of IL-18 and IL-8, and the physiopathological effect of PRT- treated convalescent plasma and in clinical trials. But, overall it appears that cFFP post-PRT were not excessively pro-inflammatory. Further research, including a careful clinical evaluation of CCP-treated patients, will be required to thoroughly define the clinical relevance of these findings.